Financial Integration in the West African Economic and Monetary Union - Sy, Amadou (IMF Working Papers; Working Paper ;, 2006)
This study assesses the degree of financial integration in the West African Economic and Monetary Union (WAEMU). The structure of the financial sector and its institutional arrangements indicate that financial integration is well advanced in some aspects. Common and foreign ownership of banks is very high and cross-border transactions are frequent in the government securities markets. Common institutions help achieve a high degree of similarity of rules. There is nonetheless scope for further financial integration as indicated by persistent deviations from the law of one price, limited cross-border bank transactions, and differences in treatment. Policy measures could therefore help achieve greater financial convergence.